Cost-effectiveness of Access to Critical Cerebral Emergency Support Services (ACCESS): a neuro-emergent telemedicine consultation program. (3rd April 2018) - Whetten, Justin; van der Goes, David N.; Tran, Huy; Moffett, Maurice; Semper, Colin; Yonas, Howard
Abstract: Aims: Access to Critical Cerebral Emergency Support Services (ACCESS) was developed as a low-cost solution to providing neuro-emergent consultations to rural hospitals in New Mexico that do not offer comprehensive stroke care. ACCESS is a two-way audio-visual program linking remote emergency department physicians and their patients to stroke specialists. ACCESS also has an education component in which hospitals receive training from stroke specialists on the triage and treatment of patients. This study assessed the clinical and economic outcomes of the ACCESS program in providing services to rural New Mexico from a healthcare payer perspective. Methods: A decision tree model was constructed using findings from the ACCESS program and existing literature, the likelihood that a patient will receive a tissue plasminogen activator (tPA), cost of care, and resulting quality adjusted life years (QALYs). Data from the ACCESS program includes emergency room patients in rural New Mexico from May 2015 to August 2016. Outcomes and costs have been estimated for patients who were taken to a hospital providing neurological telecare and patients who were not. Results: The use of ACCESS decreased neuro-emergent stroke patient transfers from rural hospitals to urban settings from 85% to 5% (no tPA) and 90% to 23% (tPA), while stroke specialist reading of patient CT/MRI imaging within 3 h of onset of stroke symptoms increased from 2% to 22%. Results indicate that use of ACCESS has the potential to save $4, 241 ($3, 952–$4, 438) per patient and increase QALYs by 0.20 (0.14–0.22). This increase in QALYs equates to ∼73 more days of life at full health. The cost savings and QALYs are expected to increase when moving from a 90-day model to a lifetime model. Conclusion: The analysis demonstrates potential savings and improved quality-of-life associated with the use of ACCESS for patients presenting to rural hospitals with acute ischemic stroke (AIS).